A 10-year study of factors associated with alcohol treatment use and non-use in a U.S. population sample. (1st March 2016) - Chartier, Karen G.; Miller, Kierste; Harris, T. Robert; Caetano, Raul
Highlights: Barriers to alcohol treatment use increased from 1991–92 to 2001–02. Increased barriers related to beliefs about stigma, treatment knowledge, and perceived need. Public insurance had a stronger relationship with treatment use at the end of the 10 years. Abstract: Background: This study seeks to identify changes in perceived barriers to alcohol treatment and predictors of treatment use between 1991–92 and 2001–02, to potentially help understand reported reductions in treatment use at this time. Social, economic, and health trends during these 10 years provide a context for the study. Methods: Subjects were Whites, Blacks, and Hispanics. The data were from the National Longitudinal Alcohol Epidemiologic Survey (NLAES) and the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). We conducted two analyses that compared the surveys on: (1) perceived treatment barriers for subjects who thought they should get help for their drinking, and (2) variables predicting past-year treatment use in an alcohol use disorder subsample using a multi-group multivariate regression model. Results: In the first analysis, those barriers that reflected negative beliefs and fears about seeking treatment as well as perceptions about the lack of need for treatment were more prevalent in 2001–02. The second analysis showed that survey year moderated the relationship between public insurance coverage and treatment use. This relationship was not statistically significant in 1991–92 but was significant and positive in 2001–02, although the effect of this change on treatment use was small. Conclusions: Use of alcohol treatment in the U.S. may be affected by a number of factors, such as trends in public knowledge about treatment, social pressures to reduce drinking, and changes in the public financing of treatment.